Analogical reasoning guidelines: a review and application to sustainable supply chains. Issue 2 (16th September 2020) - Gruner, Richard L.; Power, Damien
Abstract : Purpose: This paper aims to review analogical reasoning work to distil and apply procedural guidelines that aid theoreticians to develop novel analogies. Design/methodology/approach: The authors reviewed 189 studies from 1980 to 2020 to identify analogical reasoning guidelines. Findings: Results revealed four procedural steps for the introduction of novel analogies: target and source domain selection; domain image mapping; relevance assessment; and proposition drafting. […] shallow lakes constitute the source domain and sustainable supply chain management represents the target domain. Research limitations/implications: The identified procedural guidelines can help future scholars to develop novel analogies with rigor and structure. The paper provides an agenda for new research that addresses gaps in current studies that reason by analogy. Originality/value: This paper distils and applies analogical reasoning guidelines for the development of novel analogies, extending and complementing much existing theorizing on reasoning by analogy. Additionally, disjointed and fragmented research findings are synthesized to yield a comprehensive understanding of analogical reasoning, which can serve as a foundation for future theorizing in sustainable supply chain management and beyond.